TEORI HERMENEUTIKA PAUL RICOEUR DALAM MEMAHAMI TEKS AL-QUR’AN: TEORI HERMENEUTIKA PAUL RICOEUR DALAM MEMAHAMI TEKS AL-QUR’AN - Miftahun Najib, Muhammad (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2023)
Based on hermeneutics’ history, it is known that Paul Ricoeur brings hermeneutics into activities of interpreting and understanding texts (textual exegesis). According to Ricoeur, who is a professor of philosophy at Nanterre University, “Basically the whole philosophy is an interpretation to interpretation.” He agrees with Nietzsche that “Life itself is an interpretation. If there emerges plurality of meanings, interpretation is needed”. To study the hermeneutics of interpretation of Paul Ricoeur, we do not need to trace its root to the previous growth of this study. Richard E. Palmer even places Ricoeur’s hermeneutics separated from other previous similar studies, like the hermeneutics of sacred-book interpretation theory, hermeneutics of philology method, hermeneutics of linguistic understanding, hermeneutics of human science foundation (Geisteswissenschaften), and hermeneutics of dasein phenomenology.